Mechanical performance and water absorption resistance of HIPS/MWCNTs nanocomposite - Al-Ghamdi, Ahmed S.; Ali, Mohammad Yeakub (Trans Tech Publications, Switzerland, 2012)
The purpose of this research work is to evaluate the effects of reinforcing high impact polystyrene (HIPS’s) with multiwall carbon nanotubes (MWCNTs) on the mechanical performance and the water absorption resistance. The significant changes in HIPS/MWCNTs nanocomposite on the mechanical performance and water absorption resistance were investigated with different weight percentage of MWCNTs in the range of 0.10 wt% to 10 wt%.